Mia Mayhem gets x-ray specs - West, Kara (West, Kara. Mia Mayhem, 2020)
"Mia Mayhem is learning to control her x-ray vision! She can't wait to see through walls and crack secret codes. There's only one problem: her glasses are way too big, clunky, and totally not cool! But she knows that if she wants to keep up with her classmates, she'll have to adjust quickly. Will Mia be able to look past her obstacles and see things through?" --